Citayam Fashion Week Effect: Political and Policy Responses - Khusnul Prasetyo; Rani Lakswi Bay (Universitas Muhammadiyah Gorontalo, 2022)
This study wants to explore the extent to which the political and policy aspects work by looking at the political responses of political figures and the policy responses of policy actors. Using the desk research method as an alternative approach by using existing data sources. Data sources consist of primary, namely information collected by the researchers themselves and secondary which comes from the findings of previous studies. The results show that Citayam Fashion Week is used as a momentum for politicians to image themselves on social media with the motive of wanting to get closer to novice voters for the sake of political careers in order to gain popularity and increase electability. Policy responses are shown with appreciation and partiality, even though implementation in the field shows prohibitions. Citayam Fashion Week provides lessons on the importance of inclusive public spaces not only in Jakarta but also in other cities/regencies in Indonesia, which allows citizens to express their culture and identity safely. This is important to enrich the city's citizens' culture, economy, and social capital. Researchers also hope that the movement is not just a temporary trend, it needs a touch of designers and government intervention so that this trend can continue to grow.